The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1096/fj.202001312r
|View full text |Cite
|
Sign up to set email alerts
|

Tiam1 mediates Rac1 activation and contraction‐induced glucose uptake in skeletal muscle cells

Abstract: Contraction-stimulated glucose uptake in skeletal muscle requires Rac1, but the molecular mechanism of its activation is not fully understood. Treadmill running was applied to induce C57BL/6 mouse hind limb skeletal muscle contraction in vivo and electrical pulse stimulation contracted C2C12 myotube cultures in vitro. The protein levels or activities of AMPK or the Rac1-specific GEF, Tiam1, were manipulated by activators, inhibitors, siRNA-mediated knockdown, and adenovirus-mediated expression. Activated Rac1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…In that study, we demonstrated that calcium‐induced CaMKII activation was in part responsible for the stimulation of glucose uptake [4]. More recently, we have used EPS of C2C12 myotubes as a model of contraction to better understand the signaling pathways necessary for the stimulation of glucose uptake [18,22–24]. In the present study, we explore in greater detail how EPS‐stimulated glucose uptake involves CaMKII.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In that study, we demonstrated that calcium‐induced CaMKII activation was in part responsible for the stimulation of glucose uptake [4]. More recently, we have used EPS of C2C12 myotubes as a model of contraction to better understand the signaling pathways necessary for the stimulation of glucose uptake [18,22–24]. In the present study, we explore in greater detail how EPS‐stimulated glucose uptake involves CaMKII.…”
Section: Resultsmentioning
confidence: 86%
“…Glucose uptake was detected by measuring 2‐NBDG uptake in C2C12 myotubes as described [18]. After treatments, cells were exposed to 2‐NBDG (30 μM) in glucose‐free DMEM for 1 h at 37 °C, then cells were washed with PBS twice quickly and digested with trypsin followed by centrifugation at 1000 g for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiam1 expression was significantly increased upon Zkscan3 knockout and Zkscan3 was found to bind Tam1 promoter both in vitro and in vivo. Tiam1 is a Rac1-specific guanine nucleotide exchange factor that selectively activates Rac1 (Yue et al 2021 ). It has been reported that Tiam1 participates in cytoskeleton rearrangement, cell migration, and mobility (Zhu et al 2014 ; Izumi et al 2019 ; Payapilly et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Rho GEF Plekhg4 has been shown to promote Rac1 activation in this process [ 119 ]. Rac1 and the Rho GEFs Tiam1 and Kalirin have also been shown to mediate muscle glucose uptake in response to other stimuli [ 120 , 121 , 122 , 123 , 124 ]. It has also been posited that the RhoA–ROCK1 axis can positively influence insulin signaling in muscle and adipose cells through phosphorylation of the insulin receptor substrate 1 [ 125 , 126 , 127 ].…”
Section: Rho Gtpases Regulation Family Members and Rolesmentioning
confidence: 99%